The Board of Directors In Risk Governance - Greenhill, James (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2006)
While the Board of Directors is not expected to carry out risk management for the organization, the Board serves to prevent downfalls that could stop the organization from achieving its goals or even threaten its survival. The author shows the link between the strategic Board’s role and Enterprise Risk Management.